Impact of training in the elderly: the case of the Open Classroom for the Elderly (doctoral thesis) - José Luis Rodríguez Díez (Universidad de Cádiz, 2021)
The Senior Survey (2010) stated that in Spain 60% of people start new activities after retirement. One of the demands of this new generation of seniors is a quality university education. The purpose of this study was to investigate the impact of training in the elderly, in a formal educational context, taking into account the social and psychological dimensions. The work is structured in two sections: theoretical foundations and empirical framework.